2006
DOI: 10.1158/0008-5472.can-06-1114
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Lynch Syndrome (Hereditary Nonpolyposis Colorectal Cancer) among Endometrial Cancer Patients

Abstract: Endometrial cancer is the most common cancer in women with Lynch syndrome. The identification of individuals with Lynch syndrome is desirable because they can benefit from increased cancer surveillance. The purpose of this study was to determine the feasibility and desirability of molecular screening for Lynch syndrome in all endometrial cancer patients. Unselected endometrial cancer patients (N = 543) were studied. All tumors underwent microsatellite instability (MSI) testing. Patients with MSI-positive tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
475
6
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 569 publications
(515 citation statements)
references
References 47 publications
18
475
6
16
Order By: Relevance
“…In a previous populationbased study of colorectal and endometrial cancers, we found that 6 of 44 (13.7%) probands with LS had PMS2 mutations (these 6 mutation carriers are included in this analysis). 1,2 In the current study, we found deleterious PMS2 gene mutations in 62% of probands selected on the criterion that their tumors showed isolated loss of PMS2 protein by IHC. In addition, we found 10 probands with variants of uncertain significance in PMS2 that could be deleterious.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In a previous populationbased study of colorectal and endometrial cancers, we found that 6 of 44 (13.7%) probands with LS had PMS2 mutations (these 6 mutation carriers are included in this analysis). 1,2 In the current study, we found deleterious PMS2 gene mutations in 62% of probands selected on the criterion that their tumors showed isolated loss of PMS2 protein by IHC. In addition, we found 10 probands with variants of uncertain significance in PMS2 that could be deleterious.…”
Section: Discussionmentioning
confidence: 54%
“…In a population based study, 7 of 10 (70%) of endometrial cancer patients and 5 of 23 (22%) of colorectal cancer patients who had LS did not meet either set of published criteria. 1,2 In a population-based series of colorectal cancer patients diagnosed under age 45, 50% of LS cases would have been missed using Amsterdam criteria alone. 22 The argument could be made that given the low penetrance in monoallelic PMS2 mutation carriers, identification of probands without a family history of LS-associated tumors is not of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 MLH1 inactivating mutations lead to an approximately 20-fold increased risk of cancer development and account for 50% of Lynch syndrome cases. 5,6 However, several germline missense alterations have been identified in MLH1 whose role in the pathogenesis of colonic epithelial neoplasia is less clear.…”
mentioning
confidence: 99%
“…The term Lynch syndrome emphasizes the hereditary predisposition of malignancy that is due to germline mutation in one of the DMMR genes. Extra-colonic malignancies are especially prevalent in women with Lynch syndrome as they have a higher risk of endometrial cancer than CRC (7). The identification of Lynch syndrome families is of paramount importance as these individuals may benefit from genetic counseling, genetic testing, and more intense cancer surveillance (8).…”
Section: Introductionmentioning
confidence: 99%